Efficient Aggregation-Induced Delayed Fluorescence Luminogens for Solution-Processed OLEDs With Small Efficiency Roll-Off - Cai, Zheyi; Chen, Hao; Guo, Jingjing; Zhao, Zujin; Tang, Ben Zhong (Frontiers in Chemistry, 2020)
Purely organic small molecules with thermally activated delayed fluorescence have great potential for the application in organic light-emitting diodes (OLEDs), but overcoming severe efficiency roll-off at high voltages still remain challenging. In this work, we designed and synthesized two new emitters consisting of electron-withdrawing benzoyl and electron-donating phenoxazine and 9,9-dihexylfluorene. Their electronic structures, thermal stability, electrochemical behaviors, photoluminescence property and electroluminescence performance were thoroughly investigated. These new emitters showed weak fluorescence in dilute solution, but they could emit strong luminescence with prominent delayed fluorescence in the aggregated state, indicating the aggregation-induced delayed fluorescence (AIDF) character. The solution-processed OLEDs based on the two emitters exhibited high external quantum efficiency of 14.69%, and the vacuum-evaporation OLEDs could also provide comparable external quantum efficiency of 14.86%. Significantly, the efficiency roll-offs of these devices were very small (down to 0.2% at 1000 cd m-2), demonstrating the evidently advanced efficiency stability. These results proved that the purely organic emitters with AIDF properties could be promising to fabricate high-performance solution-processed OLEDs.